Examination of betahistine bioavailability in combination with the monoamine oxidase B inhibitor, selegiline, in humans—a non-randomized, single-sequence, two-period titration, open label single-center phase 1 study (PK-BeST) - Strupp, Michael; Churchill, Grant C.; Naumann, Ivonne; Mansmann, Ulrich; Al Tawil, Amani; Golentsova, Anastasia; Goldschagg, Nicolina (Frontiers in Neurology, 2023)
Background Betahistine was registered in Europe in the 1970s and approved in more than 80 countries as a first-line treatment for Menière's disease. It has been administered to more than 150 million patients. However, according to a Cochrane systematic review of betahistine and recent meta-analyses, there is insufficient evidence to say whether betahistine has any effect in the currently approved dosages of up to 48 mg/d. A combination with the monoamine oxidase B (MAO-B) inhibitor, selegiline, may increase the bioavailability of betahistine to levels similar to the well-established combination of L-DOPA with carbidopa or benserazide in the treatment of Parkinson's disease. We investigated the effect of selegiline on betahistine pharmacokinetics and the safety of the combination in humans. Methods In an investigator-initiated prospective, non-randomized, single-sequence, two-period titration, open label single-center phase 1 study, 15 healthy volunteers received three single oral dosages of betahistine (24, 48, and 96 mg in this sequence with at least 2 days' washout period) without and with selegiline (5 mg/d with a loading period of 7 days). Betahistine serum concentrations were measured over a period of 240 min at eight time points (area under the curve, AUC0-240 min). This trial is registered with EudraCT (2019-002610-39) and ClinicalTrials.gov. Findings In all three single betahistine dosages, selegiline increased the betahistine bioavailability about 80- to 100-fold. For instance, the mean (±SD) of the area under curve for betahistine 48 mg alone was 0.64 (+/-0.47) h*ng/mL and for betahistine plus selegiline 53.28 (+/-37.49) h*ng/mL. The half-life time of around 30 min was largely unaffected, except for the 24 mg betahistine dosage. In total, 14 mild adverse events were documented. Interpretation This phase 1 trial shows that the MAO-B inhibitor selegiline increases betahistine bioavailability by a factor of about 80 to 100. No safety concerns were detected. Whether the increased bioavailability has an impact on the preventive treatment of Menière's disease, acute vestibular syndrome, or post-BPPV residual dizziness has to be evaluated in placebo-controlled trials. Clinical trial registration https://clinicaltrials.gov/study/NCT05938517?intr=betahistine%20and%20selegiline&rank=1, identifier: NCT05938517.